Globalization challenges and opportunities: An empirical analysis of Pakistan - Shujaat Abbas; Sulaiman D. Muhammad; Shoaib Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The prime goal of this study is to evaluate the association between poverty, economic globalization and income disparity in the context of Pakistan. The pragmatic work is based on the Auto Regressive Distributed Lag (ARDL) for long run relationship and Error Correction Mechanism (ECM) approach for short run relationship testing span from 1973 to 2013. The study shows that there is long-term and short run association between Real GDP and GLOB. This study identifies the globalization's impact over inequalities in income and poverty in the context of Pakistan. The paper provides some useful and doable policy recommendations to reap maximum benefits and make globalization successful, acceptable and fruitful for Pakistan.
Keywords: 330; globalization; growth; income inequality and poverty